2008
DOI: 10.1111/j.1743-6109.2008.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Off the Nose to Save the Penis

Abstract: Introduction The average bicycle police officer spends 24 hours a week on his bicycle and previous studies have shown riding a bicycle with a traditional (nosed) saddle has been associated with urogenital paresthesia and sexual dysfunction. Aim The objective of this study was to assess the effectiveness of the no-nose bicycle saddle as an ergonomic intervention and their acceptance among male bicycle police officers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The assessment of erectile function using the Rigiscan ® has been used successfully in the occupational setting in studies of bicycle patrol officers 66121…”
Section: Assessments Of Male Reproductive Healthmentioning
confidence: 99%
“…The assessment of erectile function using the Rigiscan ® has been used successfully in the occupational setting in studies of bicycle patrol officers 66121…”
Section: Assessments Of Male Reproductive Healthmentioning
confidence: 99%
“…To evaluate the reduction in such loads pressure sensor mats resulted to be the more indicated systems and thus they have been employed in previous investigations. 10 13 From a physiological point of view the capacity of different saddle shapes to reduce perineal pressure was indirectly quantified measuring the penile oxygen pressure. 7 , 14 For this aim the most indicated instrument is the oxymeter.…”
Section: Introductionmentioning
confidence: 99%
“… Lowe, Schrader & Breitenstein (2004) applied pressure mats to bicycle seats and measured pressure distribution underlying the perineal region during stationary bicycling and concluded that the “no-nose” design reduced the pressure exerted on the perineum without leading to an increase shift in pressure on the pedals or handlebars. Schrader, Breitenstein & Lowe (2008) in a prospective study of male bicyclists who changed from a traditional “nose” seat to a “no-nose” seat for six months, noted improvements in International Index of Erectile Function Questionnaire, urogenital numbness, and penile vibrotactile sensitivity threshold.…”
Section: Discussionmentioning
confidence: 99%
“…In order to accomplish this, we devised a novel device to record pressures exerted directly on the perineum, rather than on the bicycle seat itself as has been performed in past studies. In these previous studies, it was asserted that no such technology existed to discriminate pressure exerted by the posterior regions of the thigh from the contact force affecting the soft tissues of the perineum in a real-world setting ( Schrader, Breitenstein & Lowe 2008) . By locating the perineal arteries with Doppler ultrasound probes and measuring the arterial occlusion pressure, we sought to translate the pressure exerted on the perineum during bicycle riding into a more clinically meaningful variable.…”
Section: Discussionmentioning
confidence: 99%